PROFIL E-BOOK INTERAKTIF MATERI BIOTEKNOLOGI - Ahmad Zainudin (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
The aims of this research are improvement of an interactive e-Book biotechnology. This research use Research and Development (R & D) method and tested to fifteen 3rd grade students of Madrasah Aliyah Bahauddin. Profile e-book interactive biotechnology assessed of competent lecturers.The results showed that the profile of an interactive e-Book that assessed the feasibility of some aspects of included material, presentation, and language respectively by 100%.